2002
DOI: 10.1159/000065970
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycolic Acid on UVB-Induced Skin Damage and Inflammation in Guinea Pigs

Abstract: Objectives: Recently the use of glycolic-acid-containing cosmetics has received increased public interest in their supposed ability to reduce wrinkles, roughness, age spots and other skin damage. However, the safety of such products when used excessively or chronically, especially by photosensitive people, is being questioned. The purpose of this study was to examine the effects of glycolic acid alone or in combination with UVB on skin damage and inflammatory response. Method: Guinea pigs were treated with gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Inflammatory processes in the skin produce lesions and thickening of the epidermis [30–32]. We therefore used epidermis thickness measurements in hRE slices as a marker for inflammation.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory processes in the skin produce lesions and thickening of the epidermis [30–32]. We therefore used epidermis thickness measurements in hRE slices as a marker for inflammation.…”
Section: Methodsmentioning
confidence: 99%
“…Park et al (16) reported that GA treatment at dosage of 1-7 mg ⁄ cm 2 (pH 3.0) once daily for 2 weeks immediately after UVB irradiation (0.4 and 3.0 J ⁄ cm 2 ) enhanced redness and oedema, however, did not change the basal and UVB-induced prostaglandin E 2 (PGE 2 ) production and cyclooxygenase-2 (COX-2) protein expression in guinea pig. Their dose of 1-7 mg ⁄ cm 2 was achieved by applying 10-70% of GA. As both the UVB and GA dose were rather high, skin damage such as destruction of the entire epidermis was observed, especially in the dosage of 5 and 7 mg ⁄ cm 2 .…”
Section: In Vivo Animal Studymentioning
confidence: 99%
“…But since early investigations related the process of exfoliation to mild wounding and inflammation, the interpretations of increased epidermal thickness and cell division were questionable. It now seems more certain that the effect of low concentrations of hydroxy acids does not evoke an inflammatory response 14–16 and indeed SA may even be anti‐inflammatory 17…”
Section: Biologic Propertiesmentioning
confidence: 99%
“…In animal models, topically applied GA and SA have been found to increase epidermal cell division 13,18 and in some experiments, a wave of cell proliferation has been observed 12–16 h after topical application 19 . Several authors have reported that, in human biopsy material, hydroxy acid treatment significantly increases the thickness of basal and suprabasal layers of the epidermis, while it tended to decrease the thickness of the stratum corneum 10,14,16,18–22 . Some investigators have, however, failed to observe an increase in cell division with SA treatment 7,8,23 .…”
Section: Biologic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation